The expression of microRNAs and exposure to environmental contaminants related to human health: a review. Issue 2 (1st February 2022) - Tumolo, Maria Rosaria; Panico, Alessandra; De Donno, Antonella; Mincarone, Pierpaolo; Leo, Carlo Giacomo; Guarino, Roberto; Bagordo, Francesco; Serio, Francesca; Idolo, Adele; Grassi, Tiziana; Sabina, Saverio
ABSTRACT: Environmental contaminants exposure may lead to detrimental changes to the microRNAs (miRNAs) expression resulting in several health effects. miRNAs, small non-coding RNAs that regulate gene expression, have multiple transcript targets and thereby regulate several signalling molecules. Even a minor alteration in the abundance of one miRNA can have deep effects on global gene expression. Altered patterns of miRNAs can be responsible for changes linked to various health outcomes, suggesting that specific miRNAs are activated in pathophysiological processes. In this review, we provide an overview of studies investigating the impact of air pollution, organic chemicals, and heavy metals on miRNA expression and the potential biologic effects on humans. Abbreviations : AHRR, aryl-hydrocarbon receptor repressor; AHR, aryl-hydrocarbon receptor; As, arsenic; BCL2, B-cell lymphoma 2; BCL2L11, B-cell lymphoma 2 like 11; BCL6, B-cell lymphoma 6; BPA, bisphenol A; CVD, cardiovascular diseases; CD40, cluster of differentiation 40; CCND1, Cyclin D1; CDKN1A, cyclin-dependent kinase inhibitor 1A; Cr, chromium; CTBP1, C-terminal binding protein 1; CXCL12, C-X-C motif chemokine ligand 12; DAZAP1, deleted in azoospermia associated protein 1; DEP, diesel exhaust particles; EGFR, epidermal growth factor receptor; eNOS, endothelial nitric oxide synthase; EVs, extracellular vesicles; FAK, focal adhesion kinase; FAS, fas cell surface death receptor; FOXO, forkhead box O; HbA1c, glycated hemoglobin; Hg, mercury; HLA-A, human leukocyte antigen A; HMGB, high-mobility group protein B; IFNAR2, interferon alpha receptor subunit 2; IL-6, interleukin-6; IRAK1, interleukin 1 receptor associated kinase 1; JAK/STAT, janus kinase/signal transducers and activators of transcription; MAPK, mitogen-activated protein kinase; miRNAs, microRNAs; MVs, microvesicles; NCDs, noncommunicable diseases; NFAT, nuclear factor of activated T cells; NFkB, nuclear factor kappa B; NRF2, nuclear factor, erythroid-derived 2; NRG3, neuregulin 3; O3, ozone; OP, organophosphorus pesticides; PAHs, polycyclic aromatic hydrocarbons; Pb, lead; PCBs, polychlorinated biphenyls; PDCD4, programmed cell death 4; PDGFB, platelet derived growth factor subunit beta; PDGFR, platelet-derived growth factor receptor; PI3K/Akt, phosphoinositide-3-kinase/protein kinase B; PKA, protein kinase A; PM, particulate matter; PRKCQ, protein kinase C theta; PTEN, phosphatase and tensin homolog; SORT1, sortilin 1; TGFβ, transforming growth factor-β; TLR, toll-like receptor; TNF, tumor necrosis factors; TRAF1, tumor necrosis factors-receptor associated factors 1; TRAP, traffic-related air pollution; TREM1, triggering receptor expressed on myeloid cells 1; TRIAP1, TP53 regulated inhibitor of apoptosis 1; VCAM-1, vascular cell adhesion molecule 1; VEGFA, vascular endothelial growth factor A; XRCC2, X-ray repair cross complementing 2; YBX2, Y-box-binding protein 2; ZEB1, zinc finger E-box-binding homeobox 1; ZEB2, zinc finger E-box-binding homeobox 2; 8-OH-dG, 8-hydroxy-guanine.